2014
DOI: 10.4081/ija.2014.560
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage in a semiarid Mediterranean environment: results of 20 years of research

Abstract: Conservation tillage techniques are becoming increasingly popular worldwide as they have the potential to generate environmental, agronomic, and economic benefits. In Mediterranean areas, studies performed on the effects of conservation tillage [in comparison with the conventional tillage technique (CT)] on grain yield of cereal crops have reported contradictory results as well as considerable year-to-year variation, demonstrating how the impact of different soil tillage techniques on crop productivity is stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
(36 reference statements)
5
17
3
Order By: Relevance
“…The percent recovery of 15 N fertilizer of the weed-free wheat was on average 33.9%. The values recorded in this experiment are comparable to those obtained in Tunisia by Sanaa et al ( 1992 ), in Syria by Pilbeam et al ( 1997 ), and in Italy by Giambalvo et al ( 2010 ) and by Ruisi et al ( 2014 ). López-Bellido et al ( 2006 ), in a study performed in Spain on durum wheat, reported values of labeled 15 N fertilizer recovery ranging from 12.7% when applied at sowing to 41.6% when applied as top dressing.…”
Section: Discussionsupporting
confidence: 91%
“…The percent recovery of 15 N fertilizer of the weed-free wheat was on average 33.9%. The values recorded in this experiment are comparable to those obtained in Tunisia by Sanaa et al ( 1992 ), in Syria by Pilbeam et al ( 1997 ), and in Italy by Giambalvo et al ( 2010 ) and by Ruisi et al ( 2014 ). López-Bellido et al ( 2006 ), in a study performed in Spain on durum wheat, reported values of labeled 15 N fertilizer recovery ranging from 12.7% when applied at sowing to 41.6% when applied as top dressing.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies have found that the tillage system has no effect on wheat grain protein content (Carr et al 2003;Gürsoy et al 2010). Rice et al (1986) sug-gested that low availability of N frequently observed in NT soils can sometimes be a transient effect, as observed also in other long-term experiments (Amato et al 2013;Ruisi et al 2014). It has been suggested for these reasons a supplemental (10-20%) N application in the NT systems during the conversion (2-3 years) period from CT to NT systems (Ferreira et al 2009).…”
Section: Discussionmentioning
confidence: 91%
“…The purpose of cultivation is to create optimal conditions for plants to produce a high grain yield. However, opinions about tillage systems are ambiguous, and the effects of cultivation depend on habitat conditions and sown plants [7,9,[24][25][26]. As reported by Morris et al [19], plant performance depends on many habitat and agrotechnical factors affecting each other.…”
Section: Introductionmentioning
confidence: 99%